RECOMMENDATIONS FOR EASY MEMORIZATION OF NEW WORDS IN ENGLISH - Ma'mura G'oyibnazarova Sodiqovna (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Abstract: A student who wants to get a high score in the IELTS exam for admission to foreign universities must know at least 7000 words perfectly. Scientists, writers and poets working in the English language can use 12,000-15,000 words. It is clear that regardless of the purpose and duration of learning English, you will definitely have a few thousand words you must master it. This article provides tips on how to learn new English words easily, as well as information on effective ways to learn English.